2022
DOI: 10.1002/jobm.202200274
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect and possible mechanism of phenyllactic acid on Aspergillus flavus spore germination

Abstract: Phenyllactic acid (PLA) has gained a lot of attention due to its broad antimicrobial activity, but the mechanism of its antifungal action has been barely reported until now. Herein, the inhibitory activity of PLA against Aspergillus flavus spore germination and its mechanism were preliminarily investigated. Results indicated that PLA had a strong antifungal activity against A. flavus with the minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) of 6 and 12 mg/ml, respectively. As o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
3
4
0
1
Order By: Relevance
“…aureus . These findings are also consistent with Li et al. (2022) work, implying that the response of this compound to BC contributed to the suppression of disease-causing bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…aureus . These findings are also consistent with Li et al. (2022) work, implying that the response of this compound to BC contributed to the suppression of disease-causing bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…The energy supply of the PDA in the postinfection period is limited, resulting in a decrease in protein content, whereas the grain with rich nutrition can guarantee the energy supply for 7 days. Figure 3b shows that the ATP concentration of A. flavus on the grain was higher than the concentration on PDA ( p < .05), indicating that A. flavus on grain produced more energy, and the enzymes in A. flavus were in a highly utilized state (Li et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The experiment was performed according to the instruction manual. The absorbance of all samples was obtained at 660 nm by a UV/VIS spectrophotometer (Hu et al., 2020; Li et al., 2022; Zhang et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, as an alternative to antibiotics, these LAB hold great promise for preventing mildew of silage. The inhibition activity of 3‐phenyllactic acid was related to its capacity to harm cell membranes and disrupt energy metabolism, which led to intracellular component leakage and decreased ATP synthesis, which in turn severely inhibited spore growth and even caused cell death (Li, Yao, & Meng, 2022 ). In addition, scanning electron microscope studies showed that the bacteria exposed to 3‐phenyllactic acid had damaged, even broken cell wall structure (Mu et al, 2012 ).…”
Section: Roles Of Functional Lab In Silage Prepara...mentioning
confidence: 99%